2003
DOI: 10.1002/mds.10630
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease patients with bilateral subthalamic deep brain stimulation gain weight

Abstract: Weight, body mass index (BMI) and energy expenditure/energy intake (EE/EI) was studied in 19 Parkinson's disease (PD) patients after subthalamic deep brain stimulation (STN-DBS) versus 14 nonoperated ones. Operated patients had a significant weight gain (WG, + 9.7 +/- 7 kg) and BMI increase (+ 4.7 kg/m2). The fat mass was higher after STN-DBS. Resting EE (REE; offdrug/ON stimulation) was significantly decreased in STN-DBS patients, while their daily energy expenditure (DEI) was not significantly different. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
101
9
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(136 citation statements)
references
References 27 publications
21
101
9
5
Order By: Relevance
“…Although the cause is still debated, gastrointestinal dysfunction had been suggested due to the often-occurring degeneration of the enteric nervous system during disease progression (30). It is plausible, however, that the diminished DA innervation to the CPu is the cause for the weight loss, because patients with subthalamic deep-brain stimulation gain weight after onset of treatment (31,32). To determine whether the degeneration of the nigrostriatal system in En HT mice is accompanied by lower weight, we recorded the body weight of the mutants and their En2Ϫ͞Ϫ littermate controls over their entire lifespan (Fig.…”
Section: Molecular Changes In Basal Ganglia Of En Ht Micementioning
confidence: 99%
“…Although the cause is still debated, gastrointestinal dysfunction had been suggested due to the often-occurring degeneration of the enteric nervous system during disease progression (30). It is plausible, however, that the diminished DA innervation to the CPu is the cause for the weight loss, because patients with subthalamic deep-brain stimulation gain weight after onset of treatment (31,32). To determine whether the degeneration of the nigrostriatal system in En HT mice is accompanied by lower weight, we recorded the body weight of the mutants and their En2Ϫ͞Ϫ littermate controls over their entire lifespan (Fig.…”
Section: Molecular Changes In Basal Ganglia Of En Ht Micementioning
confidence: 99%
“…Despite extensive research, there is still no unified concept explaining the mechanism of DBS-STN, namely the non-motor effects. Body weight variation has been reported in many studies as a non-motor secondary effect of DBS-STN [7][8][9][10]. Studies have shown that weight loss in patients with PD before surgery is a continuous and progressive process that starts years before a formal diagnosis is made, and that surgery modifies this state [11][12][13][14].…”
Section: Deep Brain Stimulation Of Subthalamic Nucleus (Dbs-stn) Offersmentioning
confidence: 99%
“…One of the most common chronic side-effects of DBS is weight gain (Moro et al, 1999;Barichella et al, 2003;Krack et al, 2003;Macia et al, 2004;Perlemoine et al, 2005;Kleiner-Fisman et al, 2006;Montaurier et al, 2007;Bannier et al, 2009;Sauleau et al, 2009;Walker et al, 2009;Strowd et al, 2010;Locke et al, 2011;Rieu et al, 2011). Typically, weight gain is maximal in the first year after surgery (Barichella et al, 2003;Macia et al, 2004).…”
Section: Chronic Issuesmentioning
confidence: 99%